From mouse to human: Accessing the biochemistry of vision in vivo by two-photon excitation - Palczewska, Grazyna; Wojtkowski, Maciej; Palczewski, Krzysztof (Progress in retinal and eye research, 2023)
The eye is an ideal organ for imaging by a multi-photon excitation approach, because ocular tissues such as the sclera, cornea, lens and neurosensory retina, are highly transparent to infrared (IR) light. The interface between the retina and the retinal pigment epithelium (RPE) is especially informative, because it reflects the health of the visual (retinoid) cycle and its changes in response to external stress, genetic manipulations, and drug treatments. Vitamin A-derived retinoids, like retinyl esters, are natural fluorophores that respond to multi-photon excitation with near IR light, bypassing the filter-like properties of the cornea, lens, and macular pigments. Also, during natural aging some retinoids form bisretinoids, like diretinoid-pyridiniumethanolamine (A2E), that are highly fluorescent. These bisretinoids appear to be elevated concurrently with aging. Vitamin A-derived retinoids and bisretinoidss are detected by two-photon ophthalmoscopy (2PO), using a new class of light sources with adjustable spatial, temporal, and spectral properties. Furthermore, the two-photon (2P) absorption of IR light by the visual pigments in rod and cone photoreceptors can initiate visual transduction by cis-trans isomerization of retinal, enabling parallel functional studies. Recently we overcame concerns about safety, data interpretation and complexity of the 2P-based instrumentation, the major roadblocks toward advancing this modality to the clinic. These imaging and retina-function assessment advancements have enabled us to conduct the first 2P studies with humans. [Display omitted]